EFFECTIVENESS OF THE PROCESS APPROACH IN IMPROVING WRITING: A THEORETICAL BACKGROUND - OUSKOURT, Mohammed (Journal of Human Sciences, 2008)
The purpose of this article is to provide both teachers and learners of English as a foreign language with a theoretical background about the effectiveness of the Process Approach in improving   writing. It deals with the emergence and nature of the approach. It also emphasizes the positive effects of recursiveness and that the different elements which make up writing: pre-writing, composing, drafting, revising and editing – are important composing stages